Clinical, hemodynamic and echographic characterization of diabetic patients with arterial chronic disease in lower limbs - Yoneisy Vinent Silva; Odalis García Gómez; Quiuris Acosta Franco (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The diabetes mellitus is the chronic disease considered as one of the highest sanitary emergencies in the XXI century in the world that can trigger some complications and serious health problems.  Objective: To characterize diabetic patients with arterial chronic disease in lower limbs according to clinical, hemodynamic and ultrasound variables.  Methods: An observational, descriptive and cross-sectional study of the 178 diabetic patients with clinical diagnosis of arterial chronic disease in lower limbs was carried out, who were assisted in the Imaging Service of Dr. Juan Bruno Zayas Alfonso General Hospital in Santiago de Cuba from January, 2017 to December, 2019, to whom hemodynamic exam by means of the ankle-brachial index and arterial Doppler ultrasound was carried out. Results: In the investigation there was a prevalence of the elderly (41.6 %) from the female sex (54.0 %), the intermittent abandonment as main symptom (57.3 %), the femoropopliteal sector (34.8 %) according to the exact topography of the lesions, as well as the significant stenosis (53.9 %) and the moderate peripheral arterial disease (58.3 %). Conclusions: Most of the patients presented a significant stenosis according to Doppler ultrasound, in correspondence with the diagnosis of moderated peripheral arterial disease by the ankle-brachial index. The Doppler ultrasound also contributed the exact topography of the lesions.